Age-Old Path of Russian Terminology - L. M. Alekseeva; S. L. Mishlanova (Научный диалог)
An overview of trends in the development of Russian terminology is provided in the article. The issues of the historical roots and stages of development of Russian terminology, the peculiarities of the formation of this science are highlighted, and also the evolution of its main concept “term” is revealed. It is shown that the emergence of terminology as a science correlates with the era of great Russian natural science discoveries, characterized by social challenges. It is noted that one of the prerequisites for the formation of the theory of the term is the Russian philosophical thought of the early twentieth century. An overview of terminological concepts and views is built taking into account the principle of integrity and continuity of the main stages in the development of terminology. The object and subject of terminology in dynamics are shown with an emphasis on the specifics of the development of the term science within the framework of Russian philological science. Particular attention is paid to the description of models of terminological activity in different aspects. It is pointed out that the modern stage of terminology is in the development stage. The main conclusions of the study are formulated and the prospects for the further development of Russian terminology as a science are considered. A long way of development of Russian terminology is presented, demonstrating sufficient grounds for considering it as one of the leading directions of Russian linguistic science.